What Is the effect of breast size on running economy and upper body biomechanical factors contributing to running economy? - Bennet, M. J.; Brown, N. A.; Spratford, W. A.; Lindsay, C.; Mara, J. K.; Moore, I. S.; Clark, B.; Coltman, C. E. (Medicine & Science in Sports & Exercise, 2025)
Introduction/Purpose This study investigated the effect of breast size on running economy, breast displacement, total body center of mass excursion, trunk angular velocity, and exercise-induced breast pain at different running velocities.